Alaska Native Animal Love and Nancy Lord’s Beluga Days - Benjamin Ferguson (Caliban: French Journal of English Studies)
Alaska Natives have long maintained a markedly different viewpoint toward animals from the Western mindset. Though Native communities across the Arctic have been losing connectivity with their traditions for decades, Traditional Ecological Knowledge tends to adhere to the ostensibly antithetical position of simultaneously loving and taking animals. In this article, Nancy Lord’s Beluga Days will be explored for its attempt to grasp the Native viewpoint of holistic love toward animal communities and Native discomfort with the Western mindset’s lack of nobility in treatment of animals, while carefully navigating between the two forms of animal love via journalistic travel writing. With these assertions in mind, this article will conclude with the idea that such local issues as antithetical expressions of love may benefit from what is being termed “local travel writing,” or deep investigations and travels within one’s own community.